The melanoma-associated antigen 1 (MAGEA1) protein stimulates the E3 ubiquitin-ligase activity of TRIM31 within a TRIM31-MAGEA1-NSE4 complex - Kozakova, Lucie; Vondrova, Lucie; Stejskal, Karel; Charalabous, Panagoula; Kolesar, Peter; Lehmann, Alan R; Uldrijan, Stjepan; Sanderson, Christopher M; Zdrahal, Zbynek; Palecek, Jan J (Cell Cycle, 2015)
The MAGE (Melanoma-associated antigen) protein family members are structurally related to each other by a MAGE-homology domain comprised of 2 winged helix motifs WH/A and WH/B. This family specifically evolved in placental mammals although single homologs designated NSE3 (non-SMC element) exist in most eukaryotes. NSE3, together with its partner proteins NSE1 and NSE4 form a tight subcomplex of the structural maintenance of chromosomes SMC5-6 complex. Previously, we showed that interactions of the WH/B motif of the MAGE proteins with their NSE4/EID partners are evolutionarily conserved (including the MAGEA1-NSE4 interaction). In contrast, the interaction of the WH/A motif of NSE3 with NSE1 diverged in the MAGE paralogs. We hypothesized that the MAGE paralogs acquired new RING-finger-containing partners through their evolution and form MAGE complexes reminiscent of NSE1-NSE3-NSE4 trimers. In this work, we employed the yeast 2-hybrid system to screen a human RING-finger protein library against several MAGE baits. We identified a number of potential MAGE-RING interactions and confirmed several of them (MDM4, PCGF6, RNF166, TRAF6, TRIM8, TRIM31, TRIM41) in co-immunoprecipitation experiments. Among these MAGE-RING pairs, we chose to examine MAGEA1-TRIM31 in detail and showed that both WH/A and WH/B motifs of MAGEA1 bind to the coiled-coil domain of TRIM31 and that MAGEA1 interaction stimulates TRIM31 ubiquitin-ligase activity. In addition, TRIM31 directly binds to NSE4, suggesting the existence of a TRIM31-MAGEA1-NSE4 complex reminiscent of the NSE1-NSE3-NSE4 trimer. These results suggest that MAGEA1 functions as a co-factor of TRIM31 ubiquitin-ligase and that the TRIM31-MAGEA1-NSE4 complex may have evolved from an ancestral NSE1-NSE3-NSE4 complex.
Keywords: transportní proteiny; biologické modely; domény RING-prstů; Immunoprecipitation; HEK293 Cells; Tandem Mass Spectrometry; sekvence aminokyselin; Two-Hybrid System Techniques; vazba proteinů; lidé; imunoprecipitace; Models, Biological; Molecular Sequence Data; Chromatography, Liquid; Amino Acid Sequence; HEK293 buňky; Protein Multimerization; peptidové fragmenty; Humans; Carrier Proteins; peptidy; molekulární sekvence - údaje; tandemová hmotnostní spektrometrie; ubikvitinligasy; Peptide Fragments; techniky dvojhybridového systému; Multiprotein Complexes; RING Finger Domains; nádorové proteiny; Neoplasm Proteins; multimerizace proteinu; Ubiquitin-Protein Ligases; Protein Binding; Peptides; chromatografie kapalinová; multiproteinové komplexy